MAIN INFRASTRUCTURES OF THE SYRDARYA REGION - To’rabekova Maftuna Sobirjonovna (Ecomind Press, 2025)
The economic social development of Uzbekistan is striving for rapit growth, especially due to reforms implemented on the basis of innovative infrastructure. Infrastructure is a complex systemcovering many areas, such as the introduction of new technologies, the development of science and education, the expansion of the digital services sector. The development of innovative infrastructure includes, in particular, the development and implementation of high technologies, the creation of digital infrastructure includes, in particular, the development and implementation ofhigh technjlogies, the creation of digital infrastructure, the commercialization of scientific and technical developments, as well as strengthening cooperation with the private sector economy.